Analisis Peran Kompetensi Guru terhadap Prestasi Akademik Siswa di Indonesia, Finlandia, dan China - Ratna Tri Hari Safariningsih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
The aim of this study is to investigate the relation between teacher competence and student academic achievement in Indonesia, Finland, and China. This research method is a systematic literature review of 36 journal articles. Teacher’s personal, professional, pedagogical, and social competencies are associated to student achievement in academics in Indonesia, Finland, and China. Teachers' personality competencies in China, Finland, and Indonesia are fair. Teachers' pedagogical competence in Finland and China who use technology in learning activities. Some teachers in China and Indonesia employ traditional teaching methods that only improve listening skills. Teachers with social teacher competencies in Indonesia, Finland, and China are teachers who support and assist students. Professional teacher competencies such as critical thinking, innovation, and mastery of learning materials can improve student understanding and thus student achievement.